Real-world analysis of the underdiagnosis, clinical outcomes and associated burden of hematopoietic stem cell transplantation-associated thrombotic microangiopathy (HSCT-TMA) in the United States - Wang, Yan; Rava, Andrew; Smurzynski, Marlene; Shah, Bonny; Thanataveerat, Anusorn; Al-Dakkak, Imad; Ong, Moh-Lim; Dvorak, Christopher C.; Ho, Vincent T. (Frontiers in Hematology, 2024)
BackgroundThrombotic microangiopathy (TMA) associated with hematopoietic stem cell transplantation (HSCT-TMA) is a serious post-transplant complication. Diagnosis is difficult due to overlapping symptoms with other conditions and a lack of universally adopted diagnostic criteria.MethodsThis retrospective, observational study investigated HSCT-TMA incidence between July 2009–August 2020 using the TriNetX US Electronic Medical Record database. Patients who underwent autologous or allogeneic HSCT procedures and had conditioning agents were stratified as follows: confirmed TMA (≥1 hemolytic uremic syndrome (HUS)/TMA diagnosis code), suspected TMA [no HUS/TMA code but met modified published Cho (adult) or Jodele (pediatric) diagnostic criteria (further information in main text), and non-TMA (met neither criteria). Baseline demographics, clinical characteristics and outcomes, and all-cause unadjusted healthcare resource utilization (HCRU) within 12-months of HSCT, were assessed. Statistical comparisons were against the non-TMA cohort (p<0.05).ResultsThe study included 16,809 adults and 901 pediatrics. Of these, 125 adults (0.7%) and 30 pediatrics (3.3%) had confirmed TMA, 3029 (18.0%) adults and 94 (10.4%) pediatrics had suspected TMA; 13,655 (81.2%) adults and 777 (86.2%) pediatrics met non-TMA criteria. Confirmed and suspected TMA incidences were higher after allogeneic HSCT in adults. In pediatrics, confirmed TMA incidence was higher following autologous transplantation, and suspected TMA higher after allogeneic transplantation. Confirmed and suspected TMA patients had significantly higher Charlson Comorbidity Indexes pre-HSCT and more post-HSCT complications. In adults with confirmed and suspected TMA, mortality estimates within 12-months of HSCT were significantly higher compared to non-TMA patients, and numerically higher in pediatrics. All confirmed and suspected TMA patients had significantly more ER visits, inpatient stays and ICU admissions. HCRU within 12-months of HSCT was higher in all confirmed TMA patients; ≤0.1% of patients with suspected TMA, and 25.6–50.0% of patients with confirmed TMA, received complement inhibitors.ConclusionsOur results demonstrate that incidence of HSCT-TMA in the real world, as per billing codes, is low compared with historical literature. However, a proportion of suspected TMA cases, based on diagnosis criteria, share similarly poor outcomes and HCRU. HSCT-TMA is likely underdiagnosed, or under-coded, in real world practice. Our study highlights the need for greater vigilance to this severe complication.